Concept of logistics prevention development in a defence system - Epler, Igor J.; Andrejić, Marko D.; Milenkov, Marjan A.; Sokolović, Vlada S. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Logistics prevention should be viewed as a system (composed of subsystems and components), as a function (group of related tasks grouped according to certain criteria) and as a process (course of arranged events in time). Logistics prevention is a part of the overall defence system logistics suport which prevents the infringe of projected and present performances of a supported system. Logistics prevention, as a function, includes all measures and activities planned by logistics authorities and implemented by logistics authorities and non logistics personnel. They are aimed at preventing the occurence of phenomena and processes that negatively affect the ability and performances of a defence system. At a time of intense defence system organisational changes, the approach to logistics prevention should be systematic and adequately dealt with due to its significance. The principles related to design, preparation and operation of the whole defence logistics also relate to design, preparation and implementation of logistics preventive.